EFEKTIVITAS PENGAWETAN DENGAN TEKNIK INFUS DAN BANDAGE PADA POHON BALAM TERHADAP SERANGAN RAYAP KAYU KERING - Evi Sribudiani; Esti Rini Satiti; Wa Ode Muliastuty Arsyad; Sonia Somadona; Ratih Damayanti; Djarwanto; Rudianda Sulaeman; Sulaeman Yusuf; Yusup Amin; Didi Tarmadi; Dwi Ajias Pramasari; Syafrinal (BRIN Publishing, 2021)
Currently, the availability of red meranti, kulim and mersawa wood is commonly used as raw material for “jalur” constructionin Kuansing Regency, Riau Province, are increasingly scarce, while the need is getting higher. Accordingly, it is necessary to choosealternative wood types that have similar strength and durable properties compatible with red meranti, kulim and mersawa wood tomeet specifications for the “jalur” construction. This paper studies the effectiveness of preservative treatment by infusion techniqueand bandage use against dry wood termite. Balam (Macaranga conifera Muell. Agr.) was chosen as alternative wood for makingthe path because currently this wood is abundant but not much used for making pathways. The results of field observations indicatedry-wood termites attacke the path stored on land, so it is necessary to preserve the path so that they are not attacked by wooddestroying organisms, particularly the dry-wood termites. Preservation treatments on standing trees using complex boron compoundsby infusion and bandage techniques were examined to increase the durability class of balam wood. Testing of dry-wood termiteattack was carried out according to the SNI 7207-2014 method. The data were processed using a completely randomized factorialdesign. The analysis results showed that the preservation by infusion and bandage techniques was significantly different in terms ofweight reduction and mortality of termites. Observation on the degree of attack visually on the control and infusion technique was40 (hold) lower than the bandage technique 70 (moderate). The highest mortality in infusion technique was 90.67% compared tocontrol 86.08%, and the bandage was 61.75%. Preservation using the infusion technique showed a higher boron content comparedwith the bandage technique.